Entrincheiramento ou alinhamento de interesses? Análise da oferta hostil da Sadia pelo controle da Perdigão à luz da teoria de agência - Callas, Christian (2009)
The main purpose of this paper is to study the hostile tender offer made by Sadia to takeover its main competitor Perdigão. This is a unique event in the Brazilian capital markets, once it has been made possible only due to the recent institutional e and legal reforms which created the 'Novo Mercado'. Agency Theory is the basic theoretical framework used to formulate hypothesis that would explain the refusal of the tender offer by Perdigão’s shareholders. Public information collected from the companies and in CVM are the only source of data used to analyze the adherence of the entrenchment' vs. convergence of interests' hypothesis as possible explanations to the refusal of the takeover attempt.